Micro Arc Oxidation of AZ91 Mg Alloy for Improved Corrosion Resistance - Yavuz, H.G.; Gunyuz, M.; Ozkara, Isa Metin; Baydogan, Murat; Çimenoğlu, H. (Trans Tech Publications, Ltd., 2011)
AZ91 Mg alloy was subjected to the micro arc oxidation process by using different processing parameters. Following oxidation, surface topography and qualitative phase analysis were made by tabletop digital microscopy and X-ray diffraction (XRD) analysis. In order to evaluate the relative corrosion resistance of the samples that were oxidized in different parameters, the samples were immersed in a corrosive solution for 6 days and the weight losses before and after the corrosion tests were compared. Relative corrosion resistance of the samples was evaluated on the basis of surface topography.